2019
DOI: 10.1093/jas/skz302
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter disappearance and production of short- and branched-chain fatty acids from selected fiber sources used in pet foods by a canine in vitro fermentation model1

Abstract: Dietary fibers can influence a dog’s overall health, but high concentrations of soluble dietary fibers can cause soft stools. An in vitro model could be useful to predict the rate fibers are fermented once they reach the colon. Pet food companies are constantly searching for new ingredients to differentiate their products from competitors. Miscanthus grass (MG), pea fiber (PF), and sorghum bran (SB) are novel fiber sources that could be alternatives to standards like cellulose (CE) and beet pulp (BP). The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
(84 reference statements)
1
21
2
Order By: Relevance
“…Additionally, as exercise duration increased over time, the dogs' energy requirements also increased, leading to greater feed intake and subsequently protein intake. Fecal isobutyric acid concentration was greater in Trt dogs and has been reported in dogs consuming greater levels of dietary protein ( 44 ). However, as protein contents of both diets were similar and overall feed intake did not differ between treatment groups, it is possible that the inclusion of soluble fiber reduced the digestibility of protein, thereby increasing its availability for fermentation in the colon ( 45 ).…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, as exercise duration increased over time, the dogs' energy requirements also increased, leading to greater feed intake and subsequently protein intake. Fecal isobutyric acid concentration was greater in Trt dogs and has been reported in dogs consuming greater levels of dietary protein ( 44 ). However, as protein contents of both diets were similar and overall feed intake did not differ between treatment groups, it is possible that the inclusion of soluble fiber reduced the digestibility of protein, thereby increasing its availability for fermentation in the colon ( 45 ).…”
Section: Discussionmentioning
confidence: 75%
“…Different studies have evaluated the microbial fermentation of these test substrates in dogs, both in vitro and in vivo (e.g. [6,13,[27][28][29][30][31][32][33]). However, the focus of the present study was to evaluate the fermentative capacity of food residues and to compare the effects with the microbial fermentation of the other test substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the test substrates were incubated for 24 hours, which is in accordance with the protocol of Vierbaum et al [13]. However, the incubation time in comparable studies varied from 3-72 hours [6,[27][28][29][30]33], making data comparison difficult. In addition, as beet pulp, carrot pomace and brewer´s spent grains are by-products of the food industry, their composition might differ depending on the production processes.…”
Section: Discussionmentioning
confidence: 99%
“…The animal’s digestive enzymes cannot digest fiber, unlike starch in the diet; for this reason, it contributes few, if any, calories. In the past, cellulose has been a common source of fiber in low-calorie diets [ 3 , 15 , 16 ]. Previous studies have demonstrated that poorly fermented cellulose has a moderate capacity to bind water and can decrease the transit time of food and digestibility [ 17 ], as well as increase fecal output in dogs [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%